Novel nano-crystalline Er2O3 hydrogen isotopes permeation barriers - Li, Qun; Wang, Jie; Xiang, Qing-yun; Yan, Kai; Tang, Tao; Rao, Yong-Chu; Cao, Jiang-Li (Journal of the European Ceramic Society, 2017)
Hydrogen Isotopes permeation barriers (HIPB) are used to reduce hydrogen isotopes permeation and leakage in the fields such as thermonuclear fusion energy, hydrogen energy, petroleum industry and vacuum solar receiver. In this study, nano-crystalline Er2O3 HIPB with about 5–10nm grain size were made by sol-gel method. Their performances, including deuterium-permeation reduction factor (D-PRF), micro-structure, mechanical property and electrical property were reported. The D-PRF of 0.2μm nano-crystalline Er2O3 HIPB reached 300 at 700°C and did not deteriorate after 128h deuterium permeation. The bonding strength and the nano-hardness steadily remained about 13N and 10GPa after 128h deuterium permeation at 700°C, respectively. The morphology and micro-structures of the nano-crystalline Er2O3 HIPB showed no measurable changes after 128h deuterium permeation, which ensured the stable D-PRF and mechanical properties. However, the electrical resistivity of the nano-crystalline Er2O3 HIPB decreased after deuterium permeation at 700°C. The electrical resistivity decreased from 9×109Ωcm by over three orders of magnitude and then tended to be stable, which might be attributed to oxygen loss or deuterium invasion.